Increasing Crop Output through Improved Technology Adoption: The Fadama III Approach in Delta State, Nigeria - Okeleke, CHUKWUJI Christopher (Asian Journal of Agriculture and Rural Development, 2013)
The study focused on increasing crop output through improved technology adoption: the Fadama III approach in Delta State, Nigeria. The study which took place between June 2012 and February, 2013 used stratified random sampling technique to select 340 respondents (made up of 279 Fadama users and 61 non-users). Data which came from primary source was generated through structured questionnaire and analysis was achieved by both descriptive and inferential statistics. It was shown that the rates of adoption of these technologies vary but they generally range from about 11% for Irrigation practices to about 51% for use of improved crop cultivars. The mean rate of adoption of all arable crops technologies was about 43%. Results also show that Fadama users significantly had higher mean percentage increase in yield of about 21% than non-Fadama users who recorded only a mean of about 15% increase. The variables that significantly affected rate of adoption were, Farming experience, Farm size Non-farm incomes, access to advisory services and cost of technology adoption, all of which except the last positively influenced rate of adoption. Among the constraints to adoption of technologies, cost of adoption, lack of knowledge of improved technologies, complexity of available technologies and late delivery of required improved technologies were most serious. Among other recommendations it was suggested that governments should intensify efforts to the promotion of the more adoption of proven technologies through the provision of credits in order to increase productivity.